Low‐Temperature Preferential Oxidation of Carbon Monoxide on Pt3Ni Alloy Nanoparticle Catalyst with Engineered Surface. Issue 1 (10th December 2015) - Hwang, Sang Youp; Yurchekfrodl, Eric; Zhang, Changlin; Peng, Zhenmeng
Abstract: The front cover artwork for Issue 01/2016 is provided by the catalysis research group at the University of Akron (USA). The image shows an octahedral Pt3 Ni alloy nanoparticle catalyst that benefits from unique surface geometry and electronic structure. This catalyst exhibits high activity and selectivity for the preferential oxidation of carbon monoxide in hydrogen. See the Communication itself athttp://dx.doi.org/10.1002/cctc.201500783 . Abstract : "The findings presented in this paper could be applied to many other catalytic reactions" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201500783 .